Book review: Rigg, J. 2012: Unplanned Development: Tracking Change in South-East Asia. (January 2015) - Tebboth, Mark
Rigg, J. 2012: Unplanned Development: Tracking Change in South-East Asia . London: Zed Books. 240 pp. £64.28 hardback, £17.24 paperback. ISBN: 9781848139893 (hardback), 9781848139896 (paper).